Evaluative Practices of Teachers of Special Education for Students with Intellectual Disabilities integrated into Regular Schools - Bizama, Marcela (2021)
Objective. The purpose of this research was to know the differentiated evaluation practices implemented by the special education teachers for students with special educational needs deriving from intellectual disability and are integrated into basic general education schools through the School Integration Projects (PIE). The research also analyzed the meanings that the special education teachers attribute to their own practices. Method. The research was conducted under a qualitative approach with a multiple case study design. The participants were 10 Special Education teachers in service from nine different educational establishments. The instrument used to gather information was a semi-structured interview. The information was analyzed through the thematic content analysis technique. Results. The findings show that most of the differential educators interviewed perform differentiated evaluation procedures for students with intellectual disability; these procedures are aligned with the principles of the general evaluation in order to respond to the special educational needs of the students. Conclusions. It is concluded that the centers need to conduct a reflexive analysis of teaching processes and evaluation practices that they implement in order to establish improvements in their dynamics in favor of students with intellectual disabilities who attend regular teaching centers.